Republic of Poland Financial Sector Assessment Program : Cooperative Banks and Credit Unions - International Monetary Fund; World Bank (World Bank, Washington, DC, 2019)
This technical note reviews the cooperative bank and credit union sectors. It focuses on: (i) thesituation of the two sectors that are both in states of transition; (ii) the regulatory and supervisory arrangements; and (iii) the safety net and resolution regime within the context of the crisis management framework. In addition, key perspectives are provided as to the sustainability ofinstitutional models and the sectors within a modernizing and competitive banking sector. This note was prepared using information from the authorities and market participants that was received in the first semester of 2018 at the time of the visit of the authors. Although in some instances there is subsequent improvement in the performance of some cooperative banks and credit unions, the authors believe such changes do not modify substantially the main conclusions and recommendations made. Most cooperative banks and credit unions are stable, but each sector has its own issues. The FSAP is broadly supportive of the policy direction for cooperatives, while it questions whether the credit union sector should remain standalone. Combined, cooperative banks and credit unions represent less than 8 percent of deposit takers, though more importantly they serve about 18 percent of the population.